CD8+ T-cell clones deficient in the expression of the CD45 protein tyrosine phosphatase have impaired responses to T-cell receptor stimuli. - Weaver, C T (1991)
CD45 is a high-molecular-weight transmembrane protein tyrosine phosphatase expressed only by nucleated cells of hematopoietic origin. To examine function, mouse CD8+ cytolytic T-cell clones were derived that had a specific defect in the expression of CD45. Northern (RNA) blot analysis indicates that the CD45 deficiency is due to either a transcriptional defect or mRNA instability. The CD45-deficient cells were greatly diminished in their ability to respond to antigen. All functional parameters of T-cell receptor signalling analyzed (cytolysis of targets, proliferation, and cytokine production) were markedly diminished. A CD45+ revertant was isolated, and the ability to respond to antigen was restored. These results support a central and immediate role for this transmembrane protein tyrosine phosphatase in T-cell receptor signalling.